Composite reconstruction of arm, axilla and lateral chest wall defect following resection of extensive marjolin neoplasm with an antero-lateral thigh chimeric free flap: Case report and review of literature. (2020) - Agarwal, Amit; Pandey, Neeraj; Mishra, Abhijat; Mahendru, Vihor
Abstract: Background: Marjolin's neoplasm is the most common secondary malignancy over long standing unstable burn-scar or non-healing chronic wound/ulcer. It is quite common over chest wall. Treatment of choice is radical resection and reconstruction even in advance cases to relieve patient from severe pain of cancer. Chest wall reconstruction imparts numerous challenges and extensive defects mandate the use of large micro-vascular free flaps. Selecting the most appropriate flap is important for better outcome. Method: A 45-year-old male presented with a large marjolin's neoplasm of the right lateral chest wall, developed over longstanding post electric-burn unstable scar and axillary contracture. After resection of tumour and release of contracture, resultant defect was 38 cm x 30 cm on right antero lateral and posterior aspect of chest wall and 23 cm x 10 cm defect on medial aspect of right arm and axilla with exposed brachial plexus and vessels, scapula and ribs. Reconstruction was done using left antero-lateral thigh chimeric free flap including rectus-femoris, vastus-lateralis and large fascio-cutaneous skin paddle in a single-stage procedure. The flap pedicle was anastomosed to right subclavian artery and vein. Postoperative period was uneventful with no significant deformity of the donor site. Conclusion: This case demonstrates one of the important options available for large chest wall reconstruction and shows the versatility of the Anterolateral thigh free flap as Chimeric flap. This chimeric flap ensured adequate skin cover, good bulk, provided an excellent operative position, produced little loss of donor site function and provided an acceptable cosmetic result. Level of evidence: Level 5, Case report + review of literature. Highlights: Marjolin neoplasm even in advance cases require surgical intervention. Surgical intervention can provide comfort to the patient and can improve his day to day activities. Large defect after resection requires large flap or double flap. Chimeric flap is good alternative to cover the large defect. ALT chimeric flap is best option among available flaps.